The Changing Perception of Communication Needs—A Litmus Test for the Warnock Legacy - Law, James (Frontiers in Education, 2019)
Abstract Meeting Mary Warnock at the final conference for some work commissioner by the DfEE/NHS in 2001 she said that one of her greatest concerns about her earlier report is the fetishisation of the statement of education needs. It was true that with the "statement", as it came to be known was often equated with her report, and triggered a rather legalistic culture with all the paraphernalia of tribunals and appeals. Nowhere was this more apparent than in the "border disputes" between health and education as to who was responsible for children with speech, language and communication needs (a term which only emerged twenty-five years after her report was published). I argue in this paper that the nature of disability has changed since Warnock and that communication disability is now one of the most disability conditions and communication access at least as important as physical access. Although Warnock resisted diagnostic labels in favour of "needs" there has been a burgeoning market in measures since the 1970s and with it a tendency to subcategorise children and to gain consensus in that sub-classification as witnessed by the recent work on developmental language disorder. I address the importance of seeing special needs (especially with relation to communication) through the lens of public health and, finally, look at Warnock through the recent "Bercow Ten Years On" report and argue that a focus on communication is a useful test for the consequences of the seminal report.